ERP Correlates of Simulated Purchase Decisions - Gajewski, Patrick D.; Drizinsky, Jessica; Zülch, Joachim; Falkenstein, Michael (Frontiers in Neuroscience, 2016)
Decision making in economic context is an everyday activity but its neuronal correlates are poorly understood. The present study aimed at investigating the electrophysiological brain activity during simulated purchase decisions of technical products for a lower or higher price relative to a mean price estimated in a pilot study. Expectedly, participants mostly decided to buy a product when it was cheap and not to buy when it was expensive. But in some trials they made counter-conformity decisions to buy a product for more money than the average price or not to buy a product despite an attractive price. These responses took more time and the variability of the response latency was enhanced relative to conformity responses. ERPs showed enhanced conflict related fronto-central N2 during both types of counter-conformity compared to conformity decisions. A reverse pattern was found for the P3a and P3b. The response-locked P3 (r-P3) was larger and the subsequent CNV smaller for counter-conformity than conformity decisions. We assume that counter-conformity decisions elevate the response threshold (larger N2), intensify response evaluation (r-P3) and attenuate the preparation for the next trial (CNV). These effects were discussed in the framework of the functional role of the fronto-parietal cortex in economic decision making.